The Development of Science, Technology, Engineering, Arts and Mathematics Nuanced Mathematics Teaching Materials to Improve Mathematical Conceptual Understanding Ability - Putri, Ade Andani; Asikin, Muhammad (Unnes Journal of Mathematics Education, 2021)
This research is a development research that aims to develop mathematics teaching materials related to Science, Technology, Engineering, Arts, and Mathematics (STEAM). This study uses the stages of Research and Development (R&D) covering potential and problems; data collection; product design; design validation (potential test and feasibility test); product test (readability test and attractiveness test); use trials (effectiveness test) and the final product. The results of the study indicate that teaching materials have the potential to improve the ability of mathematical conceptual understanding; valid, easy to understand, attractive in appearance, and effectively improve the ability of mathematical conceptual understanding. The test results show that teaching materials have the potential to increase the ability of mathematical conceptual understanding with a percentage of 86.5%. The results of the feasibility test show that the teaching materials are valid for use with a percentage of 86.07%. The results of the readability test showed that the teaching materials were easily understood by students with a percentage of 92.26%. The results of the response test showed that the teaching materials were attractive in appearance with a percentage of 90.15%. Then, the results of the effectiveness test showed that the teaching materials were effective in increasing the ability of mathematical conceptual understanding.